2015
DOI: 10.4240/wjgs.v7.i3.43
|View full text |Cite
|
Sign up to set email alerts
|

Successful emergency resection of a massive intra-abdominal hemophilic pseudotumor

Abstract: An intra-abdominal pseudotumor is a rare complication of hemophilia. Surgical treatment is associated with high morbidity and mortality rates and reported cases are scarce. We present a 66-year-old Caucasian male suffering from severe hemophilia type A treated for 10 years with Factor VIII. Major complications from the disease were chronic hepatitis B and C, cerebral hemorrhage and disabling arthropathy. Twenty-three years ago, retro-peritoneal bleeding led to the development of a large intra-abdominal pseudot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…These are shown in Table 2. The most commonly occurring complications were infection (25% of complications reported), 5,13,14,16 fistula formation (25%) [12][13][14]43,44 and issues regarding wound healing and failure of surgery (18%). 5,8,10,12,16 Significant bleeding events happened in seven patients (16%) in the postoperative period.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…These are shown in Table 2. The most commonly occurring complications were infection (25% of complications reported), 5,13,14,16 fistula formation (25%) [12][13][14]43,44 and issues regarding wound healing and failure of surgery (18%). 5,8,10,12,16 Significant bleeding events happened in seven patients (16%) in the postoperative period.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Doyle et al evaluated the available HPT treatment options associated with haemophilia [ 67 ]. The authors collected 48 articles: 40 single case reports, seven single centre case series, and one multicentre case series [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. They concluded that “timely surgical intervention with adequate haemodynamic support and the consideration of adjuvant therapies in selected cases can achieve acceptable outcomes in this cohort of patients”.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudotumors most often occurs in the long bones (especially the femur) and the pelvis in adults hemophilic patients, while in children with hemophilia pseudotumors usually affects the immature bones of limbs [4] , [5] . As the pseudotumor grows, it will cause progressive compression of the major nerve and vascular compression, fatal massive hemorrhage, pathological fractures and intestinal obstruction [6] , [7] , [8] , [9] . Although there has been extensive research on the treatment of hemophilia.…”
Section: Introductionmentioning
confidence: 99%